2019
DOI: 10.18502/fid.v16i2.1360
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Propolis Nanoparticles on Antimicrobial Properties and Shear Bond Strength of Orthodontic Composite Bonded to Bovine Enamel

Abstract: Objectives:This study sought to assess the effect of curcumin nanoparticles (curcNPs) on antimicrobial property and shear bond strength (SBS) of orthodontic composite to bovine enamel.Materials and Methods:In this in vitro, experimental study, 1%, 5% and 10% curcNPs were added to Transbond XT composite. Stainless steel brackets were bonded to 48 sound bovine incisors in four groups (n=12) using composite containing 0% (control), 1%, 5% and 10% curcNPs. The bracket-tooth SBS was measured by a universal testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 38 publications
(42 reference statements)
8
56
1
1
Order By: Relevance
“…Although these results pointed to greater antibacterial capacity for high concentrations of TiO 2 against S. mutans and S. sanguinis, the effect obtained was far less against L. acidophilus. But the study by Sodagar et al [83] did not follow the same pattern; samples showed less antibacterial potential than Sodagar et al [16], while samples modified with CurcNP showed better results against L. acidophilus, regardless of the CurcNP concentration [83]. These findings could mean that TiO 2 nanoparticles are more effective against S. mutans and S. sanguinis colonies, and CurcNP nanoparticles are more effective against L. acidophilus, although further research with a more clearly defined protocol is required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Although these results pointed to greater antibacterial capacity for high concentrations of TiO 2 against S. mutans and S. sanguinis, the effect obtained was far less against L. acidophilus. But the study by Sodagar et al [83] did not follow the same pattern; samples showed less antibacterial potential than Sodagar et al [16], while samples modified with CurcNP showed better results against L. acidophilus, regardless of the CurcNP concentration [83]. These findings could mean that TiO 2 nanoparticles are more effective against S. mutans and S. sanguinis colonies, and CurcNP nanoparticles are more effective against L. acidophilus, although further research with a more clearly defined protocol is required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 94%
“…Streptococcus mutans and Lactobacillus acidophilus are mainly responsible for the appearance of caries, and for this reason most of the studies reviewed used these bacteria in antibacterial tests. Even so, certain studies used other microorganisms in their antibacterial tests, such as Escherichia coli [25,59,66,67,74,79], Staphylococcus aureus [5,59,66,67,74,79], Pseudomonas aeruginosa [59,67,74], Streptococcus sobrinus [2,8,60], Streptococcus sanguinis [12,16,83], Staphylococcus epidermidis [67], Streptococcus oralis [2,66], Streptococcus gordonii [2], Actinomyces naeslundii [2,76], Candida krusei [66], Porphyromonas gingivalis [45,46,53], Prevotella intermedia [45,46,53], Prevotella nigrescens [45,53], Aggregatibacter actinomycetemcomitans [45,46,53], Fusobacterium nucleatum [45,46,53], Enterococcus faecalis [45,53,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations